Characterization of a Ribonucleic Acid Polymerase Activity Associated with Purified Cytoplasmic Polyhedrosis Virus of the Silkworm Bombyx mori - Lewandowski, L. J. (1969)
Purified cytoplasmic-polyhedrosis virus has been found to have associated with it a polymerase activity capable of catalyzing the synthesis of virus-specific, single-stranded ribonucleic acid (RNA) from the double-stranded RNA genome.